2017
DOI: 10.1007/s00127-017-1339-3
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness and depression in the elderly: the role of social network

Abstract: Purpose. Loneliness and depression are associated, in particular in older adults. Less is known about the role of social networks in this relationship. The present study analyzes the influence of social networks in the relationship between loneliness and depression in the older adult population in Spain. Results. Feelings of loneliness were more prevalent in women, those who were younger (50-65), single, separated, divorced or widowed, living in a rural setting, with a lower frequency of social interactions an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
230
5
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 348 publications
(310 citation statements)
references
References 39 publications
26
230
5
12
Order By: Relevance
“…Regression analysis revealed that depression among AMWs was related to young age, poor self‐rated physical health, moderate‐to‐severe pain, fair and poor family relationships, having no good friend at the same factory, and working under high pressure. Overall, these findings are similar to those reported in existing studies about depression in the general population, which identify chronic physical conditions, pain, social disconnectedness, and job stress as significant risk factors for depression (Domènech‐Abella et al, ; Patten, Williams, Lavorato, et al, ; Wang et al, ; Wu et al, ). There are, however, some disparities.…”
Section: Discussioncontrasting
confidence: 77%
“…Regression analysis revealed that depression among AMWs was related to young age, poor self‐rated physical health, moderate‐to‐severe pain, fair and poor family relationships, having no good friend at the same factory, and working under high pressure. Overall, these findings are similar to those reported in existing studies about depression in the general population, which identify chronic physical conditions, pain, social disconnectedness, and job stress as significant risk factors for depression (Domènech‐Abella et al, ; Patten, Williams, Lavorato, et al, ; Wang et al, ; Wu et al, ). There are, however, some disparities.…”
Section: Discussioncontrasting
confidence: 77%
“…A previous study by Victor et al [43] showed that older women living alone were more likely than those with others to experience feeling of social isolation partly because of a lack of social network including emotional support. Improved social relationships were connected with reduced level of loneliness [43] which was associated with depression [44, 45]. Compared to community involvement, individual relationship is more informal and therefore older women living alone can be dependent principally on individual relationship for emotional support.…”
Section: Discussionmentioning
confidence: 99%
“…Although the IOM report focused on measures of social connection and isolation, loneliness was considered a subcomponent of these measures, and several different measures of loneliness have been used to establish its relevance to health and risk for mortality. Loneliness may be easily identified using the UCLA three‐item loneliness scale (Supplementary Table S1) . Efforts are underway to incorporate this loneliness screen into EHRs.…”
Section: Epidemiologymentioning
confidence: 99%